Method for preparing ceramsite adsorption material by coupling gasification slag with biochar
The ceramic adsorption materials are prepared by gasified slag coupled with biochar, and the electrostatic and chemical adsorption mechanisms of functionalized biochar and modified liquid are used to solve the problems of land resource waste and environmental pollution in the treatment of coal gasified slag, and the ceramics are improved The adsorption capacity and chelation properties of the materials meet the needs of the construction industry and reduce the risk of environmental pollution.
Patent Information
- Application Number
- CN202411401710.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-09
AI Technical Summary
In the prior art, the treatment method of coal gasified coarse slag has problems of land resources and environmental pollution, and the adsorption capacity and compatibility of the ceramic material are insufficient to meet the actual needs.
The method of preparing ceramic adsorption materials by gasified slag coupled biochar is used to prepare clay adsorption materials by adding functionalized biochar and modified liquid, and electrostatic and chemical adsorption is used to utilize hydroxyl, ester, amide, benzene ring and epoxy structures to improve adsorption Capacity and chelation performance, and the adsorption capacity is enhanced by forming a three-dimensional interoperability network structure through the modification liquid.
It significantly improves the adsorption capacity of the ceramic adsorption materials and the chelating properties of metal ions, avoids the dissolution of heavy metals in sludge biochar, meets the needs of the construction industry and reduces the risk of environmental pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid waste resource utilization, and specifically relates to a method for preparing ceramsite adsorption material by coupling gasified slag with biochar. Background Art
[0002] Coal gasification slag is a mixture formed by coal powder being gasified at high temperature and high pressure, and is a solid waste produced by coal gasification technology. Coal gasification slag is mostly disposed of by stockpiling and landfilling, which not only wastes land resources but also causes serious environmental health problems. Therefore, the comprehensive utilization of coal gasification slag resources has received widespread attention. Related studies have found that coal gasification slag is mainly composed of SiO2, Al2O3, CaO, Fe2O3, and C, and its main mineral phase is amorphous silicate, mixed with quartz, calcite, etc., which meets the requirements of ceramsite production raw materials.
[0003] The methods for preparing ceramsite materials in the prior art mainly include high-temperature roasting method and non-fired method. Although the ceramsite materials prepared by the high-temperature roasting method have high strength and density and can meet the needs of the construction industry, the high temperature of 1000°C required for sintering the ceramsite will cause the internal pores of the raw materials to collapse, and the content of active ingredients will be significantly reduced, resulting in a decrease in its adsorption capacity. At the same time, existing studies have shown that ceramsite with good adsorption capacity can be prepared by the non-fired method using fly ash or sludge biochar as raw materials, but the sludge biochar containing heavy metals in the production raw materials of sludge ceramsite will inevitably dissolve during use, causing secondary pollution to the environment. At the same time, in the process of preparing the ceramsite adsorption material by the non-fired method, the compatibility between the pore-forming agent and the substrate is poor. The adsorption capacity of the ceramsite adsorption material obtained by mechanical stirring alone is poor and cannot meet actual needs. Summary of the invention
[0004] In order to produce a product with good chelating performance for metal ions and high adsorption capacity while avoiding the large-scale dissolution of heavy metals in sludge biochar in the raw materials, the present application provides a method for preparing ceramsite adsorption material by coupling gasification slag with biochar.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, preparing the following raw materials in parts by weight: 68-72 parts of coal gasification slag, 9-12 parts of cement, 8-10 parts of sodium silicate water glass, 6-8 parts of expanded perlite, 14-20 parts of functionalized biochar, 130-150 parts of modified liquid and 0.1-0.2 parts of initiator; Step S2, preparing a formed ceramsite rough embryo: grinding and sieving the coal gasification slag to obtain coal gasification slag powder, uniformly mixing the coal gasification slag powder, cement, sodium silicate water glass, expanded perlite and functionalized biochar by weight to obtain ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing treatment until the particle size meets the standard, aging at room temperature for 1-2 hours, drying, and maintaining at a constant temperature to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: mix the initiator and the modifying liquid to obtain a modifier, then immerse the formed ceramsite rough embryo obtained in step S2 in the modifier, heat it to 74-78°C, react for 1-2h, continue to heat it to 175-185°C, and carbonize it for 12-14h. After the reaction is completed, wash and dry it to obtain the ceramsite adsorption material.
[0006] Preferably, in step S2, the qualified particle size of the rough pellets is 5-8 mm.
[0007] Preferably, in step S2, the initiator is ammonium persulfate or potassium persulfate.
[0008] Preferably, the modified liquid is prepared by the following method: Step A1, at room temperature, add glucose and ferrous sulfate to deionized water in a mass ratio of 12-16:6-8:75:16-20, heat to 35-45°C, stir evenly, continue stirring and dropwise add a mixture of KH-550 and anhydrous ethanol, continue stirring for 12-16 hours, filter, wash and dry to obtain a modified monomer, wherein the mass ratio of KH-550 to anhydrous ethanol in the mixture a is 0.3-0.5:20; Step A2, dissolving the modified monomer in anhydrous ethanol at a mass ratio of 3-6:35-45:0.16-0.18, adding 1-allyl-3-methylimidazolium trifluoromethanesulfonate, stirring evenly, and obtaining a modified liquid.
[0009] Preferably, the functionalized biochar is prepared by the following method: Step B1, mixing the sludge biochar and a 30% calcium nitrate solution at a mass ratio of 11-13:1, drying to constant weight, and then heating to 550-650°C, and keeping the temperature for reaction for 10-16 minutes to obtain modified biochar; in the above reaction process, the abundant silicon dioxide in the sludge biochar carrier reacts with calcium oxide to generate Ca-O-Si during high-temperature pyrolysis, thereby improving the dispersion stability of the calcium-based material in the modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol in a mass ratio of 5:10:0.32-0.54:20-24, stirring evenly, heating to 50-60°C, stirring and reacting for 6-8h, centrifuging, washing and drying the precipitate to obtain epoxy biochar; Step B3, adding epoxy biochar to DMF at a mass ratio of 5:35-45:20, stirring evenly, adding tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF mixed solution b dropwise, heating to 90-110°C, continuing to stir and react for 2-3 hours, centrifuging after the reaction, washing the precipitate, and drying to obtain functionalized biochar; wherein, in the mixed solution b, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF is 1:8-12:100, and in the above reaction process, epoxy biochar and α-acetylaminocinnamic acid are used as raw materials, and tetrabutylammonium bromide is used as a catalyst to cause the epoxy biochar and α-acetylaminocinnamic acid to undergo a ring-opening esterification reaction to obtain functionalized biochar with hydroxyl groups, acylamino groups and unsaturated double bonds bonded on the surface.
[0010] Compared with the prior art, the present invention has the following beneficial effects: in order to improve the adsorption capacity of the prepared ceramsite adsorption material and avoid the dissolution of heavy metal ions in sludge biochar causing secondary pollution to the environment, the present invention starts from two aspects. One is to add functionalized biochar, which contains hydroxyl, ester, amide, benzene ring and epoxy biochar structures. The presence of hydroxyl, ester, amide and benzene ring can physically adsorb heavy metal cations through electrostatic action and van der Waals force, thereby avoiding the dissolution of heavy metal ions. The epoxy biochar is KH-560 modified biochar loaded with calcium oxide. On the one hand, the presence of biochar gives the functionalized biochar a similar structure to coal gasification slag, thereby enhancing the compatibility of calcium oxide in the functionalized biochar with coal gasification slag. , which improves the adsorption capacity of the expanded clay adsorption material. On the other hand, the siloxane group on KH-560 can produce chemical bonds with the hydroxyl groups on the surface of the gasification slag after hydrolysis, further improving the compatibility of calcium oxide in the functionalized biochar with the gasification slag, and further improving the adsorption capacity of the expanded clay adsorption material. Secondly, the modified liquid is added. On the one hand, the imidazole group and trifluoromethanesulfonic acid group on it can chelate with heavy metal cations through electrostatic action and van der Waals force. On the other hand, the presence of unsaturated double bonds on it can chemically cross-link with the double bonds in the functionalized biochar to form a three-dimensional interconnected network structure. Introducing it into the expanded clay adsorption material can synergize with the functionalized biochar to jointly improve the adsorption capacity of the expanded clay adsorption material and its chelating performance for metal ions. DETAILED DESCRIPTION
[0011] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0012] The processes, conditions, reagents, experimental methods, etc. for implementing the present application, except for those specifically mentioned below, are common knowledge and common common sense in the art and are not particularly limited by the present invention.
[0013] The cement is ordinary silicate No. 425 cement produced by Shanshui Cement; the mass concentration of sodium silicate water glass is 34%, and the modulus is 1.6; the sludge biochar is produced from the sludge pyrolysis carbonization production line of the Institute of Urban Environment, Chinese Academy of Sciences in Tongan Wastewater Treatment Plant, Xiamen; the gasification slag comes from a gasification plant in Datong City, Shanxi Province; the expanded perlite comes from Hebei Yixin Energy Saving and Insulation Building Materials Company.
[0014] The contents of the main raw materials and their components used in the examples are as follows: Table 1 Main chemical composition of raw materials used in this application / %
[0015] Preparation Examples 1-3 and Comparative Preparation Example 1 provide methods for preparing functionalized biochar.
[0016] Preparation Example 1 Functionalized biochar is prepared by the following method: Step B1, according to the mass ratio of 11:1, the sludge biochar and the calcium nitrate solution with a mass fraction of 30% were stirred at a speed of 400 rpm for 35 minutes until uniform, dried at 50°C to constant weight, and then heated to 550°C at a rate of 5°C / min and kept warm for 16 minutes to obtain modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol at a mass ratio of 5:10:0.32:20, stirring at a speed of 500 rpm for 30 minutes until uniform, heating to 50°C, maintaining the speed unchanged, stirring and reacting for 6 hours, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water three times in sequence, and drying at 60°C to constant weight to obtain epoxy biochar; Step B3, add epoxy biochar to DMF at a mass ratio of 5:35:20, stir at a speed of 600 rpm for 20 minutes until uniform, maintain the speed unchanged, continue stirring and drop tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF mixed solution b, control the dropwise addition within 30 minutes, and after the dropwise addition is completed, heat to 90°C, continue stirring and react for 3 hours. After the reaction is completed, centrifuge and precipitate, then use anhydrous ethanol and deionized water for 3 times in sequence, and dry to obtain functionalized biochar, wherein, in the mixed solution b, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF is 1:8:100.
[0017] Preparation Example 2 Functionalized biochar is prepared by the following method: Step B1, according to the mass ratio of 11-13:1, the sludge biochar and the calcium nitrate solution with a mass fraction of 30% are mixed at a speed of 450 rpm and stirred for 30 minutes until uniform, dried at 55°C to constant weight, and then heated to 600°C at a rate of 5°C / min, and kept warm for 14 minutes to obtain modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol at a mass ratio of 5:10:0.43:22, stirring at a speed of 550 rpm for 25 min until uniform, heating to 55°C, maintaining the speed unchanged, stirring and reacting for 7 h, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water for 4 times in sequence, and drying at 65°C to constant weight to obtain epoxy biochar; Step B3, add epoxy biochar to DMF at a mass ratio of 5:40:20, stir at a speed of 550 rpm for 25 minutes until uniform, maintain the speed unchanged, continue stirring and drop tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF mixed solution b, control the dropwise addition within 30 minutes, and after the dropwise addition, heat to 100°C and stir for 2.5 hours. After the reaction is completed, the precipitate is washed with anhydrous ethanol and deionized water for 4 times in sequence, and dried at 65°C to constant weight to obtain functionalized biochar; wherein, in the mixed solution b, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF is 1:10:100.
[0018] Preparation Example 3 Functionalized biochar is prepared by the following method: Step B1, according to a mass ratio of 13:1, the sludge biochar and the calcium nitrate solution with a mass fraction of 30% were stirred at a speed of 500 rpm for 25 minutes until uniform, dried at 60°C to constant weight, and then heated to 650°C at a rate of 5°C / min and kept warm for 10 minutes to obtain modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol at a mass ratio of 5:10:0.54:24, stirring at a speed of 650 rpm for 20 min until uniform, heating to 60°C, maintaining the speed unchanged, stirring and reacting for 8 h, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water for 5 times in sequence, and drying at 70°C to constant weight to obtain epoxy biochar; Step B3, add epoxy biochar to DMF at a mass ratio of 5:45:20, stir at a speed of 500 rpm for 20 minutes until uniform, maintain the speed unchanged, continue stirring and drop tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF mixed solution b, after the dropwise addition, heat to 110°C and stir for 2 hours. After the reaction is completed, centrifuge, wash the precipitate with anhydrous ethanol and deionized water for 5 times in sequence, and dry at 70°C to constant weight to obtain functionalized biochar; wherein, in the mixed solution b, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF is 1:12:100.
[0019] Comparative Preparation Example 1 Functionalized biochar is prepared by the following method: Step B1, according to a mass ratio of 11:1, the sludge biochar and the zinc nitrate solution with a mass fraction of 30% were stirred at a speed of 400 rpm for 35 minutes until uniform, dried at 50°C to constant weight, and then heated to 550°C at a rate of 5°C / min and kept warm for 10 minutes to obtain modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol at a mass ratio of 5:10:0.32:20, stirring at a speed of 500 rpm for 30 minutes until uniform, heating to 50°C, maintaining the speed unchanged, stirring and reacting for 6 hours, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water three times in sequence, and drying at 60°C to constant weight to obtain epoxy biochar; Step B3, add epoxy biochar to DMF at a mass ratio of 5:35:20, stir at a speed of 600 rpm for 20 minutes until uniform, maintain the speed unchanged, continue stirring and drop tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF mixed solution b, control the dropwise addition within 30 minutes, and after the dropwise addition is completed, heat to 90°C, continue stirring and react for 3 hours. After the reaction is completed, centrifuge and precipitate, then use anhydrous ethanol and deionized water for 3 times in sequence, and dry to obtain functionalized biochar, wherein, in the mixed solution b, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF is 1:8:100.
[0020] Comparative Preparation Example 2 Functionalized biochar is prepared by the following method: Step B1, according to a mass ratio of 11:1, the sludge biochar and the calcium nitrate solution with a mass fraction of 30% were stirred at a speed of 400 rpm for 35 minutes until uniform, dried at 50°C to constant weight, and then heated to 550°C at a rate of 5°C / min and kept warm for 10 minutes to obtain modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol at a mass ratio of 5:10:0.32:20, stirring at a speed of 500 rpm for 30 minutes until uniform, heating to 50°C, maintaining the speed unchanged, stirring and reacting for 6 hours, centrifuging, and washing the precipitate with anhydrous ethanol and deionized water three times in sequence, and drying at 60°C to constant weight to obtain epoxy biochar; Step B3, add epoxy biochar to DMF at a mass ratio of 5:35:20, stir at a speed of 600 rpm for 20 minutes until uniform, maintain the speed unchanged, continue stirring and drop tetrabutylammonium bromide, benzoic acid and DMF mixed solution b, control the dropwise addition within 30 minutes, and after the dropwise addition is completed, heat to 90°C, continue stirring and react for 3 hours. After the reaction is completed, centrifuge and precipitate, then use anhydrous ethanol and deionized water for 3 times in sequence, and dry to obtain functionalized biochar, wherein, in the mixed solution b, the mass ratio of tetrabutylammonium bromide, benzoic acid and DMF is 1:8:100.
[0021] Preparation Examples 4-6 and Comparative Preparation Example 3 provide methods for preparing modified liquids.
[0022] Preparation Example 4 The modified liquid is prepared by the following method: Step A1, at room temperature, add glucose and ferrous sulfate to deionized water in a mass ratio of 12:6:75:16, heat to 35°C, stir at a speed of 400 rpm for 35 minutes until uniform, maintain the speed unchanged, continue stirring and dropwise add a mixture of KH-550 and anhydrous ethanol a, control the dripping within 30 minutes, maintain the speed unchanged, continue stirring for 16 hours, filter, and then wash with anhydrous ethanol and deionized water three times in sequence, and dry at 55°C to constant weight to obtain a modified monomer, wherein, in the mixture a, the mass ratio of KH-550 to anhydrous ethanol is 0.3:20; Step A2, add the modified monomer to anhydrous ethanol at a mass ratio of 3:35:0.16, stir at a speed of 450 rpm for 20 minutes until uniform, then add 1-allyl-3-methylimidazole trifluoromethanesulfonate, maintain the speed unchanged, and continue stirring for 2.5 hours to obtain a modified solution.
[0023] Preparation Example 5 The modified liquid is prepared by the following method: Step A1, at room temperature, add glucose and ferrous sulfate to deionized water in a mass ratio of 14:7:75:18, heat to 40°C, stir at a speed of 500 rpm for 25 minutes until uniform, maintain the speed unchanged, continue stirring and dropwise add a mixture of KH-550 and anhydrous ethanol, and control the dripping to be completed within 30 minutes. After the dripping is completed, continue stirring for 14 hours, filter, and then wash with anhydrous ethanol and deionized water 4 times in sequence, and dry at 60°C to constant weight to obtain a modified monomer, wherein, in the mixture a, the mass ratio of KH-550 to anhydrous ethanol is 0.4:20; Step A2, add the modified monomer to anhydrous ethanol at a mass ratio of 4.5:40:0.17, stir at a speed of 500 rpm for 25 minutes until uniform, then add 1-allyl-3-methylimidazolium trifluoromethanesulfonate, maintain the speed unchanged, and continue stirring for 3 hours until uniform to obtain a modified liquid.
[0024] Preparation Example 6 The modified liquid is prepared by the following method: Step A1, at room temperature, add glucose and ferrous sulfate to deionized water in a mass ratio of 16:8:75:20, heat to 45°C, stir at a speed of 600 rpm for 15 minutes until uniform, maintain the speed unchanged, continue stirring and dropwise add a mixture of KH-550 and anhydrous ethanol, and control the dripping to be completed within 30 minutes. After the dripping is completed, maintain the speed unchanged, continue stirring for 12 hours, filter, and then wash with anhydrous ethanol and deionized water for 5 times in sequence, and dry at 60°C to constant weight to obtain a modified monomer, wherein, in the mixed solution a, the mass ratio of KH-550 to anhydrous ethanol is 0.5:20; Step A2, add the modified monomer to anhydrous ethanol at a mass ratio of 6:45:0.18, stir at a speed of 550 rpm for 20 minutes until uniform, then add 1-allyl-3-methylimidazolium trifluoromethanesulfonate, continue stirring for 4 hours until uniform, and obtain a modified liquid.
[0025] Comparative Preparation Example 3 The modified liquid is prepared by the following method: Step A1, at room temperature, add glucose and ferrous sulfate to deionized water in a mass ratio of 12:6:75:16, heat to 35°C, stir at a speed of 400 rpm for 35 minutes until uniform, maintain the speed unchanged, continue stirring and dropwise add a mixture of KH-550 and anhydrous ethanol a, control the dripping within 30 minutes, maintain the speed unchanged, continue stirring for 16 hours, filter, and then wash with anhydrous ethanol and deionized water three times in sequence, and dry at 55°C to constant weight to obtain a modified monomer, wherein, in the mixture a, the mass ratio of KH-550 to anhydrous ethanol is 0.3:20; Step A2, add the modified monomer to anhydrous ethanol at a mass ratio of 3:35:0.16, stir at a speed of 450 rpm for 20 minutes until uniform, then add allyl cyclohexane, maintain the speed unchanged, and continue stirring for 2.5 hours to obtain a modified liquid.
[0026] Example 1 A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, preparing the following raw materials in parts by weight: 68 parts of coal gasification slag, 9 parts of cement, 8 parts of sodium silicate water glass, 6 parts of expanded perlite, 14 parts of functionalized biochar prepared in Preparation Example 1, 130 parts of modified liquid prepared in Preparation Example 4, and 0.1 parts of ammonium persulfate; Step S2, preparing a formed ceramsite rough embryo: grinding the coal gasification slag, passing it through a 100-mesh sieve to obtain coal gasification slag powder, stirring the coal gasification slag powder, cement, sodium silicate water glass, expanded perlite and functionalized biochar at a speed of 500 rpm for 25 minutes until uniform, to obtain a ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing machine for a pelletizing treatment to a particle size of 5 mm, aging at room temperature for 1 hour, drying at 80° C. for 2 hours, and then curing at a constant temperature of 100° C. for 8 hours to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: Stir the ammonium persulfate and the modifying liquid at a speed of 400 rpm for 30 minutes until uniform to obtain a modifier, then immerse the molded ceramsite rough embryo obtained in step S2 in the modifier, heat to 74°C, react for 1 hour, continue to heat to 175°C, and carbonize for 12 hours. After the reaction is completed, wash with anhydrous ethanol and deionized water three times in sequence, and then dry at 75°C for 4 hours to obtain a ceramsite adsorption material.
[0027] Example 2 A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, preparing the following raw materials in parts by weight: 70 parts of coal gasification slag, 10.5 parts of ordinary silicate No. 425 cement, 9 parts of sodium silicate water glass, 7 parts of expanded perlite, 17 parts of functionalized biochar prepared in Preparation Example 2, 140 parts of modified liquid prepared in Preparation Example 5, and 0.15 parts of potassium persulfate; Step S2, preparing a formed ceramsite rough embryo: grinding the coal gasification slag, passing it through a 100-mesh sieve to obtain coal gasification slag powder, stirring the coal gasification slag powder, ordinary silicate No. 425 cement, sodium silicate water glass, expanded perlite and functionalized biochar at a speed of 550 rpm for 20 min until uniform, to obtain a ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing machine for a pelletizing treatment to a particle size of 6 mm, aging at room temperature for 1.5 h, drying at 110° C. for 1.5 h, and then curing at a constant temperature of 100° C. for 8 h to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: Stir potassium persulfate and the modifying liquid at a rotation speed of 450 rpm for 25 minutes until uniform to obtain a modifier, then immerse the molded ceramsite rough embryo obtained in step S2 in the modifier, heat to 76°C, react for 1.5 hours, continue to heat to 180°C, and carbonize for 13 hours. After the reaction is completed, wash with anhydrous ethanol and deionized water for 4 times in sequence, and then dry at 80°C for 3 hours to obtain a ceramsite adsorption material.
[0028] Example 3 A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, prepare the following raw materials in parts by weight: 72 parts of coal gasification slag, 12 parts of ordinary silicate No. 425 cement, 10 parts of sodium silicate water glass, 8 parts of expanded perlite, 20 parts of functionalized biochar prepared in Preparation Example 3, 150 parts of modified liquid prepared in Preparation Example 6, and 0.2 parts of ammonium persulfate; Step S2, preparing a formed ceramsite rough embryo: grinding the coal gasification slag, passing it through a 100-mesh sieve to obtain coal gasification slag powder, stirring the coal gasification slag powder, ordinary silicate No. 425 cement, sodium silicate water glass, expanded perlite and functionalized biochar at a speed of 600 rpm for 15 min until uniform, to obtain a ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing machine for a pelletizing treatment to a particle size of 8 mm, aging at room temperature for 2 h, drying at 95° C. for 1.8 h, and then curing at a constant temperature of 100° C. for 8 h to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: ammonium persulfate and the modifying liquid are stirred at a rotation speed of 500 rpm until uniform to obtain a modifier, and then the molded ceramsite rough embryo obtained in step S2 is immersed in the modifier, heated to 78°C, reacted for 2 hours, and continued to heat to 185°C, carbonized for 14 hours. After the reaction is completed, it is washed with anhydrous ethanol and deionized water for 5 times in sequence, and then dried at 85°C for 2.5 hours to obtain a ceramsite adsorption material.
[0029] In order to verify the comprehensive performance of the ceramsite adsorption materials produced in Examples 1-3 of the present application, the present application sets up Comparative Examples 1-3.
[0030] Comparative Example 1 A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, preparing the following raw materials in parts by weight: 68 parts of coal gasification slag, 9 parts of cement, 8 parts of sodium silicate water glass, 6 parts of expanded perlite, 14 parts of functionalized biochar prepared in Comparative Preparation Example 1, 130 parts of modified liquid prepared in Preparation Example 4, and 0.1 parts of ammonium persulfate; Step S2, preparing a formed ceramsite rough embryo: grinding the coal gasification slag, passing it through a 100-mesh sieve to obtain coal gasification slag powder, stirring the coal gasification slag powder, cement, sodium silicate water glass, expanded perlite and functionalized biochar at a speed of 500 rpm for 25 minutes until uniform, to obtain a ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing process in a pelletizing machine until the particle size meets the standard, aging at room temperature for 1 hour, drying at 80° C. for 2 hours, and then curing at a constant temperature of 100° C. for 8 hours to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: Stir the initiator and the modifying liquid at a speed of 400 rpm for 30 minutes until uniform to obtain a modifier, then immerse the molded ceramsite rough embryo obtained in step S2 in the modifier, heat it to 74°C, react for 1 hour, continue to heat it to 175°C, and carbonize it for 12 hours. After the reaction is completed, wash it with anhydrous ethanol and deionized water three times in sequence, and then dry it at 75°C for 4 hours to obtain a ceramsite adsorption material.
[0031] Comparative Example 2 A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, preparing the following raw materials in parts by weight: 68 parts of coal gasification slag, 9 parts of cement, 8 parts of sodium silicate water glass, 6 parts of expanded perlite, 14 parts of functionalized biochar prepared in Comparative Preparation Example 2, 130 parts of modified liquid prepared in Preparation Example 4, and 0.1 parts of ammonium persulfate; Step S2, preparing a formed ceramsite rough embryo: grinding the coal gasification slag, passing it through a 100-mesh sieve to obtain coal gasification slag powder, stirring the coal gasification slag powder, cement, sodium silicate water glass, expanded perlite and functionalized biochar at a speed of 500 rpm for 25 minutes until uniform, to obtain a ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing process in a pelletizing machine until the particle size meets the standard, aging at room temperature for 1 hour, drying at 80° C. for 2 hours, and then curing at a constant temperature of 100° C. for 8 hours to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: Stir the initiator and the modifying liquid at a speed of 400 rpm for 30 minutes until uniform to obtain a modifier, then immerse the molded ceramsite rough embryo obtained in step S2 in the modifier, heat it to 74°C, react for 1 hour, continue to heat it to 175°C, and carbonize it for 12 hours. After the reaction is completed, wash it with anhydrous ethanol and deionized water three times in sequence, and then dry it at 75°C for 4 hours to obtain a ceramsite adsorption material.
[0032] Comparative Example 3 A method for preparing ceramsite adsorption material by coupling gasified slag with biochar comprises the following steps: Step S1, preparing the following raw materials in parts by weight: 68 parts of coal gasification slag, 9 parts of cement, 8 parts of sodium silicate water glass, 6 parts of expanded perlite, 14 parts of the functionalized biochar prepared in Preparation Example 1, 130 parts of the modified liquid prepared in Comparative Preparation Example 3, and 0.1 parts of ammonium persulfate; Step S2, preparing a formed ceramsite rough embryo: grinding the coal gasification slag, passing it through a 100-mesh sieve to obtain coal gasification slag powder, stirring the coal gasification slag powder, cement, sodium silicate water glass, expanded perlite and functionalized biochar at a speed of 500 rpm for 25 minutes until uniform, to obtain a ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing process in a pelletizing machine until the particle size meets the standard, aging at room temperature for 1 hour, drying at 80° C. for 2 hours, and then curing at a constant temperature of 100° C. for 8 hours to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: Stir the initiator and the modifying liquid at a speed of 400 rpm for 30 minutes until uniform to obtain a modifier, then immerse the molded ceramsite rough embryo obtained in step S2 in the modifier, heat it to 74°C, react for 1 hour, continue to heat it to 175°C, and carbonize it for 12 hours. After the reaction is completed, wash it with anhydrous ethanol and deionized water three times in sequence, and then dry it at 75°C for 4 hours to obtain a ceramsite adsorption material.
[0033] The following performance tests are performed on the ceramsite adsorption materials prepared in Examples 1-3 and Comparative Examples 1-3: 1. Leaching toxicity test Referring to HJ557-2010 "Solid Waste Leaching Toxicity Leaching Method - Horizontal Oscillation Method" and leaching standards (US-EPA), the leaching toxicity experiment of ceramsite adsorption material was carried out, and the heavy metal TCLP leaching amount (mg / L) of ceramsite leaching solution was determined by atomic absorption spectrophotometry. The specific test results are shown in Table 2 below: Table 2
[0034] It can be seen from Table 2 that although the heavy metal ion content of the ceramsite adsorption materials prepared in Examples 1-3 and Comparative Examples 1-3 meets the requirements of the "Hazardous Waste Identification Standard Leaching Toxicity Identification" (GB5085.3-2007) standard, the leaching rate of heavy metal ions of the ceramsite adsorption materials prepared in Examples 1-3 is much lower than that of Comparative Examples 1-3, which indicates that the ceramsite adsorption materials prepared in the present application have better chelating properties for metal ions.
[0035] 2. Adsorption CIP test 3 g of the ceramsite adsorption material prepared in Examples 1-3 and Comparative Examples 1-3 were respectively weighed and placed in a 250 mL conical flask containing 100 mL of a potassium dihydrogen phosphate solution with an initial phosphorus mass concentration of 5 mg / L, sealed with a plastic film and placed in a constant temperature oscillator, and an adsorption test was carried out at 35 ° C and a speed of 120 r / min. The residual phosphorus mass concentration in the solution after adsorption was determined by ammonium molybdate spectrophotometry. The specific test results are shown in Table 3 below: Table 3
[0036] It can be seen from the data shown in Table 3 that compared with comparative examples 1-3, the ceramsite adsorption materials prepared in Examples 1-3 of the present application have higher adsorption capacity.
[0037] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing ceramsite adsorption material by coupling gasified slag with biochar, characterized in that: The following steps are involved: Step S1, preparing the following raw materials in parts by weight: 68-72 parts of coal gasification slag, 9-12 parts of cement, 8-10 parts of sodium silicate water glass, 6-8 parts of expanded perlite, 14-20 parts of functionalized biochar, 130-150 parts of modified liquid and 0.1-0.2 parts of initiator; Step S2, preparing a formed ceramsite rough embryo: grinding and sieving the coal gasification slag to obtain coal gasification slag powder, uniformly mixing the coal gasification slag powder, cement, sodium silicate water glass, expanded perlite and functionalized biochar by weight to obtain ceramsite slurry, and then subjecting the prepared ceramsite slurry to a pelletizing treatment until the particle size meets the standard, aging at room temperature for 1-2 hours, drying, and maintaining at a constant temperature to obtain a formed ceramsite rough embryo; Step S3, modification with a modifier: the initiator and the modifying liquid are mixed to obtain a modifier, and the molded ceramsite rough embryo obtained in step S2 is immersed in the modifier, the temperature is raised to 74-78° C., the reaction is carried out for 1-2 hours, the temperature is further raised to 175-185° C., the carbonization reaction is carried out for 12-14 hours, and after the reaction is completed, the ceramsite adsorption material is washed and dried to obtain; The functionalized biochar is prepared by combining sludge biochar and calcium nitrate to obtain modified biochar, which is then modified by KH-560 to obtain epoxy biochar, and finally combined with α-acetylaminocinnamic acid. The modified liquid is prepared by mixing glucose and ferrous sulfate, modifying with KH-550 to obtain a modified monomer, and then mixing with 1-allyl-3-methylimidazole trifluoromethane sulfonate.
2. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 1, characterized in that: The modified liquid is prepared by the following method: Step A1, at room temperature, add glucose and ferrous sulfate to deionized water in a mass ratio of 12-16:6-8:75:16-20, heat to 35-45°C, stir evenly, continue stirring and dropwise add a mixture of KH-550 and anhydrous ethanol, continue stirring for 12-16 hours, filter, wash and dry to obtain a modified monomer; Step A2, dissolving the modified monomer in anhydrous ethanol at a mass ratio of 3-6:35-45:0.16-0.18, adding 1-allyl-3-methylimidazolium trifluoromethanesulfonate, stirring evenly, and obtaining a modified liquid.
3. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 1, characterized in that: The functionalized biochar is prepared by the following method: Step B1, mixing the sludge biochar and a 30% calcium nitrate solution at a mass ratio of 11-13:1, drying to constant weight, heating to 550-650°C, and keeping the temperature for 10-16 minutes to obtain modified biochar; Step B2, adding modified biochar, deionized water and KH-560 to anhydrous ethanol in a mass ratio of 5:10:0.32-0.54:20-24, stirring evenly, heating to 50-60°C, stirring and reacting for 6-8h, centrifuging, washing and drying the precipitate to obtain epoxy biochar; Step B3, add epoxy biochar to DMF at a mass ratio of 5:35-45:20, stir evenly, add tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF mixed solution b dropwise, raise the temperature to 90-110°C, continue stirring and reacting for 2-3 hours, and after the reaction is completed, centrifuge, wash the precipitate, and dry to obtain functionalized biochar.
4. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 1, characterized in that: In the step S2, the standard particle size of the rough pellets is 5-8 mm.
5. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 1, characterized in that: In step S2, the initiator is ammonium persulfate or potassium persulfate.
6. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 2, characterized in that: In the mixed solution a, the mass ratio of KH-550 to anhydrous ethanol is 0.3-0.5:
20.
7. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 3, characterized in that: In the step B1, the temperature is raised to 550-650° C. at a rate of 5° C. / min and kept at this temperature for 10 minutes.
8. The method for preparing ceramsite adsorption material by coupling gasified slag with biochar according to claim 3, characterized in that: In the mixed solution b, the mass ratio of tetrabutylammonium bromide, α-acetylaminocinnamic acid and DMF is 1:8-12:100.
Citation Information
Patent Citations
A Water-retaining Agent of Oil-tea Camellia Dregs Biochar and Its Applications in Soil Improvements
AU2020101477A4
One-pot method for preparing alpha-acetamidocinnamic acid
CN101747224A
Preparation method and application of high adsorption performance water supply plant residual mud non-sintered ceramsite
CN108178605A
Unfired ceramsite and preparation method thereof
CN111548111A
Soil conditioner and application thereof, and soil conditioning and / or soil remediation method
CN112111282A
